The role of heterogenous implementation on the uptake and long-term diffusion of agricultural insurance in a pastoral context - Jensen, Nathaniel D.; Teufel, Nils; Banerjee, Rupsha R.; Galgallo, Diba; Shikuku, Kelvin Mashisia (Elsevier, 2024)
To make a difference in lower-income countries, agricultural innovations must be adopted and ultimately diffused across diverse local environments. This study contributes to the ongoing debate about the factors limiting the spread of agricultural innovations by considering the role of heterogenous supply in determining observed demand for the Index-Based Livestock Insurance (IBLI) product, which is a commercial insurance product serving historically uninsured pastoralists in the Horn of Africa. Analysis of sales data from 2010 to 2020 in Ethiopia and Kenya shows that local conditions can reduce the likelihood of supply channels reaching prospective clients, effectively excluding them from accessing insurance, while other factors can work towards increasing supply of insurance while also decreasing demand for it. Surveys collected from insurance sales agents reveals considerable heterogeneity in their ability to and effort in suppling IBLI. Discussions with IBLI’s providers confirms the role of supply constraints in observed demand; the firms consistently point towards the cost of last-mile extension and sales as their largest challenge to increasing sales, and emphasize that it is cost-prohibitive to provide equal access to well-trained insurance agents across the areas that they operate. These findings suggest that current investments aimed at increasing insurance coverage by increasing demand, for example through improved product design or by subsidizing premiums, should be accompanied by investments in developing more cost-effective marketing and distribution processes so that demand can be acted upon. On a broader level, the results highlight a need to consider non-random and incomplete supply as a factor when examining observed uptake of agricultural innovations.